Good Governance Program Bantuan Langsung Tunai Dana Desa (BLT-DD) di Desa Cukanggalih Kecamatan Curug Kabupaten Tangerang - Waratri, Hesti Dwi; Asmawi, Muhammad Rosul; Mazya, Thita Moralitha (Innovative: Journal Of Social Science Research, 2024)
Implementation of a Good Governance System in the Village Fund Direct Cash Assistance Program (BLT-DD) in Cukanggalih Village, Curug District, Tangerang Regency. With the post-covid 19 phenomenon, poverty is still a challenge for the government to eradicate extreme poverty which has made the government continue the BLT-Village Fund program. The purpose of this study is to determine how good governance the Village Fund Direct Cash Assistance (BLT-DD) program is in Cukanggalih Village, Curug District, Tangerang Regency. This study uses a qualitative research method. Data were collected using observation, interview, and documentation techniques. Types and sources of data are primary data and secondary data. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. Research location Cukanggalih Village, Curug District, Tangerang Regency The theoretical concept used is the Principles Good Governance Indicator in the UNDP (1997) which focuses on 5 Principles out of 9 principles including Participation, Rule of Law, Transparency, Fairness and accountability. Based on the results of the study, it can be concluded that most of them have been implemented quite well. However, in the principle of participation, there are still obstacles in the form of a lack of utilization of village websites as digital information media services that need special attention.